Scotland Embarks on a National Outdoor Play Initiative: Educator Perspectives. Issue 7 (3rd October 2021) - Howe, Nina; Perlman, Michal; Bergeron, Catherine; Burns, Samantha
ABSTRACT: Research Findings . The Scottish government is in the process of transforming their early childhood learning and care landscape by doubling the number of free hours of childcare for families and by requiring that all children in care spend a significant portion of each day outdoors. Thus, the government is promoting outdoor play programs. We surveyed 45 educators working in 16 outdoor programs and 16 nursery programs in Scotland as this transition was taking place. The survey focused on the benefits, barriers, risks, and challenges regarding implementation of this new social policy and educators' views on an ideal outdoor play program. Research Findings and Policy revealed that educators working in outdoor play programs were more confident in supporting outdoor play, reported more benefits, risks, and challenges for both children and educators, and highlighted more barriers to implementing the new policy. Educators in both programs held similar views about early learning and care programs reflecting Ministry play-based curriculum guidelines for children's learning, development, and the role of educators. Only outdoor play program educators raised issues regarding risk benefit analysis of outdoor play. Our findings highlight the importance of considering the views of educators regarding government policy decisions and its potential success of implementation.